2016
DOI: 10.1111/bjep.12122
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an early‐intervention, computer‐based literacy program to boost phonological skills in 4‐ to 6‐year‐old children

Abstract: An early-intervention, computer-based literacy program can be effective in boosting the phonological skills of 4- to 6-year-olds, particularly if these literacy difficulties are not linked to phonological working memory deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Furthermore, the adaptive component of the online instruction in this study ensured students optimized their time by focusing on specific skills where they needed extra practice. Outcomes consistent with this study were recently reported by O'Callaghan et al (2016) when Core5 was implemented outside of the United States as part of an intervention study with at-risk 4-to 6-year olds in Northern Ireland.…”
Section: Benefits Of Blended Learningsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the adaptive component of the online instruction in this study ensured students optimized their time by focusing on specific skills where they needed extra practice. Outcomes consistent with this study were recently reported by O'Callaghan et al (2016) when Core5 was implemented outside of the United States as part of an intervention study with at-risk 4-to 6-year olds in Northern Ireland.…”
Section: Benefits Of Blended Learningsupporting
confidence: 89%
“…The blended learning approach utilized in this study, Lexia Reading Core5 Ò (Core5; Lexia Learning 2014) was chosen based on prior studies of demonstrated efficacy (Schechter et al 2017;Schechter et al 2015;O'Callaghan et al 2016) as well as features that address key areas of effective instruction, including clear objectives, frequent assessments of student progress, personalized learning, and ample opportunities for exposure to academic printed materials (Espinoza 2008;Francis et al 2006;Goldenberg 2012). The program is designed to accelerate reading skills in students who are behind their peers as well as sustain and increase progress for on-level and above-level readers.…”
Section: Blended Learning Approach Used In Study Schoolsmentioning
confidence: 99%
“…Fletcher and Nicholas (2016) argued that curriculum subjects require different albeit comparable approaches to content delivery, whereby the materials are developed to match the expected reading ability for each grade. Although O'Callaghan et al (2016) showed reduced support for literacy programs in low-performing school districts, a comparable analysis in Australia reveals that the socio-cultural profiles of individual students do not negatively influence their perceptions towards learning (Fletcher & Nicholas, 2016). The research revealed that the analyzed student populations were more dependent on teacher attitudes for determining the views that they had regarding the importance of literacy skills.…”
Section: Teacher and Student Perception Of Early Literacy Skillsmentioning
confidence: 81%
“…A recent study presented the blended model as capable of increasing gains for all grades through to Grade 7, with Grade 2 students showing the highest literacy gains compared to other grades (Prescott, Bundschuh, Kazakoff, & Macaruso, 2017). Moreover, individual programs such as Lexia Reading Core2 show gains in non-word reading and subsequently improved scores for at-risk students whose learning difficulties were not a result of deficits in working memory (O'Callaghan, McIvor, McVeigh, & Rushe 2016). This illustrates the need for instructors to consider implementing these programs for literacy interventions to ensure that they can achieve comparable gains for low-reading at-risk students in their classrooms.…”
Section: Struggling Reader Characteristics/interventionsmentioning
confidence: 99%
“…Lexia Core5. In a randomized control trial, O'Callaghan, McIvor, McVeigh, and Rushe (2016) found that Pre-K and kindergarten students who participated in Lexia made higher gains in both phonological awareness and fluency than their peers who received standard classroom instruction. However, the researchers noted that students did not see the same gains in phonemic awareness and that about one-third of the students did not…”
Section: Research On the Impact Of Lexia Core5mentioning
confidence: 99%